Pembentukan Sikap Toleransi Siswa Melalui Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Multikultural di SMAN 2 Mataram - Aryanti Dwiyani; Eva Sofia Sari (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
In this paper, the problem studied is the formation of student tolerance through multicultural-based Islamic Religious Education (PAI) learning in public schools. This study puts forward religious values, namely tolerance. The importance of multicultural-based Islamic Religious Education (PAI) not only instills religious values ​​in students, but also fosters an attitude of tolerance and inclusiveness (openness) in progress. In addition, there is still a lack of understanding of tolerance, difference, diversity, and progress in the lives of students, which causes the occurrence of multicultural values ​​in schools to be lost and not properly actualized. The flow of modernization and globalization is also one part that affects the multicultural crisis in students. An attitude of tolerance, respect and respect for every difference is the basic capital for students in responding to and understanding every difference in life, because this is very much in line with the values ​​of Islamic teachings, namely respecting every difference between fellow humans. Thus the tolerant attitude taught in learning Islamic religious education can provide an understanding of the meaning and meaning of each progression so that students avoid exclusivity (closed), consider themselves the most right and think others are wrong. The research method used is qualitative research with data collection techniques using observation, interviews and documentation and is supported by various relevant references. This paper provides an alternative, namely